2022
DOI: 10.3389/fneur.2022.865690
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the TMEM151A Gene in Patients With Paroxysmal Kinesigenic Dyskinesia and Other Movement Disorders

Abstract: BackgroundParoxysmal kinesigenic dyskinesia (PKD) is a rare neurological disorder characterized by recurrent involuntary movements usually triggered by sudden movements. Mutations in the TMEM151A gene were found to be the causative factor of PKD in recent studies. It has also been revealed that loss-of-function is the mechanism by which TMEM151A mutations cause PKD.MethodsTo investigate the genetic basis of PKD and broaden the clinical spectrum of the TMEM151A mutations, we recruited 181 patients of Chinese or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Wirth et al [22] reported a de novo mutation in TMEM151A in a patient with PKD. Ma et al [14] reported two novel TMEM151A variants from two families, while Wang et al [20] also identi ed a novel variant in four individuals from one pedigree. They described the typical manifestations of PKD in a three-generation family and suggested that the TMEM151A gene may be associated with the disease spectrum of PKD-PKD/ICbenign familial infantile convulsions (BFIC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wirth et al [22] reported a de novo mutation in TMEM151A in a patient with PKD. Ma et al [14] reported two novel TMEM151A variants from two families, while Wang et al [20] also identi ed a novel variant in four individuals from one pedigree. They described the typical manifestations of PKD in a three-generation family and suggested that the TMEM151A gene may be associated with the disease spectrum of PKD-PKD/ICbenign familial infantile convulsions (BFIC).…”
Section: Discussionmentioning
confidence: 99%
“…TMEM151A, located at 11q13.2 and encoding transmembrane protein 151A, was rst reported as causative for PKD in 2021 [12]. Subsequent studies have shown that patients with TMEM151A variants are phenotypically different to patients with PRRT2 variants [2,13,14,16,20,22], the former more likely to be sporadic, have shorter attacks, and present with dystonia [2]. Like the PRRT2 protein, TMEM151A is also highly expressed in the brain, markedly increasing in expression postnatally, peaking at postnatal day 14, and then declining in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…PRRT2 mutations account for 77% to 93% of familial cases and 21% to 45% of sporadic cases in different cohorts 7,8 . In 2021, heterozygous transmembrane protein 151A ( TMEM151A ) variants were verified in both familial and sporadic cases in Chinese and French PKD cohorts 9‐14 . Variants of other genes, such as PNKD , SLC2A1 , KCNA1 , SCN8A , and DEPDC5 , were also detected in patients with PKD 15‐17 .…”
Section: Introductionmentioning
confidence: 98%
“…7,8 In 2021, heterozygous transmembrane protein 151A (TMEM151A) variants were verified in both familial and sporadic cases in Chinese and French PKD cohorts. [9][10][11][12][13][14] Variants of other genes, such as PNKD, SLC2A1, KCNA1, SCN8A, and DEPDC5, were also detected in patients with PKD. [15][16][17] However, there is still a large proportion of patients with PKD with unclear genetic causes.…”
Section: Introductionmentioning
confidence: 99%
“…TMEM151A, located at 11q13.2 and encoding transmembrane protein 151A, was rst reported as causative for PKD in 2021 [12]. Subsequent studies have shown that patients with TMEM151A variants are phenotypically different to patients with PRRT2 variants [2,13,14,16,20,22], the former more likely to be sporadic, have shorter attacks, and present with dystonia [2]. Like the PRRT2 protein, TMEM151A is also highly expressed in the brain, markedly increasing in expression postnatally, peaking at postnatal day 14, and then declining in adulthood.…”
Section: Introductionmentioning
confidence: 99%